SAT0015 ROCK INHIBITION REDUCES THE SEVERITY OF K/BXN SERUM-TRANSFER INDUCED ARTHRITIS. (2nd June 2020) - Rodríguez-Trillo, A.; Mosquera Garrote, N.; Pena Pena, C. M.; Mera Varela, A.; Gonzalez, A.; Conde, C.
Abstract : Background: Fibroblast-like synoviocytes (FLS) are pivotal in inflammation and joint damage of rheumatoid arthritis (RA). These cells acquire an aggressive and invasive phenotype and secrete inflammatory mediators, metalloproteases and cathepsins that perpetuate inflammation and lead to cartilage and bone damage. We have previously shown that non-canonical Wnt5a pathway is involved in the aggressive phenotype of FLS by increasing their migration and invasion ability, and by stimulating the inflammatory response. The non-canonical Wnt signaling pathway included the planar cell polarity (PCP), with the activation of Rho and Rac GTPases, and the Wnt/Ca2+ pathways. We have also shown that Wnt5a contributes to the aggressive phenotype of RA FLS by binding to RYK receptor, through Rho-ROCK pathway and the activation of MAPKs, ERK and P38, as well as the activation of AKT and GSK3β. Objectives: To elucidate the therapeutic potential of the ROCK inhibitor (Y-27632) in the K/BxN serum transfer arthritis model. Methods: Two groups of C57BL/6J mice were used, in the control group, mice were treated with physiological serum and in the experimental group with a ROCK inhibitor (Y-27632). Arthritis was induced by intraperitoneal injection of 100 µl of K/BxN serum on days 0 and 2. In the experimental group, mice were treated with intraperitoneal injections of 10 mg/kg from day 0 until sacrifice, on day 10. Control mice were treated with the same volume of physiological serum. Arthritis was assessed by two observers using a semiquantitative clinical score. For histological analysis, it was decided to obtain the right ankle joints and foot. Joints were fixed in formalin for 6h and were decalcified and embedded in paraffin. Sections were stained with hematoxylin and eosin (H&E) and toluidine. Finally, total RNA was obtained from wrist and ankle joints of mice and the expression of inflammatory mediators and metalloproteases was analyzed by real-time PCR. Results: Arthritis was induced in C57BL/6J mice, which were treated with Y-27632 (ROCK inhibitor) or with physiological serum. The incidence of arthritis was 100% in both groups of mice and there were no differences in the course of the disease. Clinical score was significantly lower in the Y-27632-treated mice, all along the follow-up, compared with controls. Similar results were observed in the histological analysis. We also analyzed the effect of ROCK inhibitor on the inflammatory response of K/BxN serum-transfer induced arthritis. This analysis revealed that expression of IL6, IL1β, CXCL1, MMP3, MMP9 and MMP13 were significantly decreased in Y-27632-treated mice compared with control mice. In addition, TNF and NOS2 expression was reduced in Y-27632-treated mice to reach the same levels that observed in C57BL/6J mice without arthritis. Conclusion: These results indicate that the inhibition of the Rho-ROCK pathway decreases the severity of arthritis in the K/BxN serum transfer model, and point to ROCK as potential therapeutic target for RA. Supported: ISCIII / PI17 / 01660 / RETICS Program, RD16 / 0012/0014 / Cofinanced FEDER. Disclosure of Interests: None declared